2016
DOI: 10.3233/bmr-160671
|View full text |Cite
|
Sign up to set email alerts
|

Three week results of transforaminal epidural steroid injection in patients with chronic unilateral low back related leg pain: The relation to MRI findings and clinical features

Abstract: Abstract. BACKGROUND:Transforaminal epidural steroid injection (TESI) is a frequently used intervention for lumbar radicular pain. OBJECTIVE: To evaluate the value of MRI findings, neurologic assessment and the Slump test (neurodynamic test) as predictors of treatment response to TESI. METHOD: One hundred subjects (mean age 58 [SD13], 54% females) were included in this trial. The sample was stratified by location of disc herniaton, grade of nerve root compression, clinically assessed neurologic deficit and pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
(62 reference statements)
1
5
0
1
Order By: Relevance
“…In addition, Ekedahl et al [21] found that high-grade nerve root compression was a strong predictor of adverse treatment outcomes during one-year follow-up. On the other hand, some authors have suggested that there is no correlation between spinal nerve root compression and treatment response [13,19], and this was consistent with our study findings. In our study we included patients with subarticular/central herniation and excluded those with foraminal herniation; therefore, we were unable to evaluate foraminal compression.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, Ekedahl et al [21] found that high-grade nerve root compression was a strong predictor of adverse treatment outcomes during one-year follow-up. On the other hand, some authors have suggested that there is no correlation between spinal nerve root compression and treatment response [13,19], and this was consistent with our study findings. In our study we included patients with subarticular/central herniation and excluded those with foraminal herniation; therefore, we were unable to evaluate foraminal compression.…”
Section: Discussionsupporting
confidence: 93%
“…This indicates that there are several factors which affect treatment success. A number of studies have been carried out to investigate the clinical and radiological parameters which can affect TFESI outcomes [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. These studies have shown that the duration of symptoms before TFESI has an effect on treatment outcomes with an inverse correlation between duration of pretreatment symptoms and treatment outcomes [11,16,21].…”
Section: Introductionmentioning
confidence: 99%
“…However, a central canal stenosis observed on MRI may be associated with increased odds of a positive response, even though the association was not statistically significant in multivariate analysis. These associations have been disputed in previous studies [19,22,23,27,28]. Other variables, including age, sex, the presence of trauma or sprain, the location of pain, neurogenic claudication and findings of physical examination, cannot be considered as predictors of short-term outcome after a TFESI.…”
Section: Discussionmentioning
confidence: 97%
“…Despite the widespread availability of epidural steroid injections, little is known about the factors predicting their success. Studies investigating the predictors of lumbar epidural steroid injections have shown conflicting results [9,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28]. If the diagnostic information can be used to predict treatment response, it can facilitate the treatment plan.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with nociceptive LBLP (Ekedahl et al, 2016;Harrisson et al, 2017;Konstantinou et al, 2018), aged 18-65 years, were recruited at the department of neurosurgery from the University Hospital Brussels. Patients with lumbar radicular nociceptive pain, with an indication for spine surgery, were contacted to participate (Adebajo and Fabule, 2012).…”
Section: Participantsmentioning
confidence: 99%